Analisis kebangkrutan pada PT. Garuda Indonesia Tbk. Dengan Menggunakan Model Springate - Budi Dharma; Shelvi Fadillah Harahap (Bursa : Jurnal Ekonomi dan Bisnis, 2023)
Every business always tries to make a profit, so the financial health of the business needs to be maintained so that it runs well. However, companies must be able to foresee the possibility of bankruptcy. Bankruptcy analysis is carried out to get early warning of bankruptcy. One of the tools used to predict the potential for bankruptcy of a company is the Springate S-Score method. The purpose of this research is to find out the financial performance of PT. Garuda Tbk for the 2019-2022 period and if there is a potential for bankruptcy. This research method uses qualitative. Data collection techniques with documentation studies. The analysis technique uses the Springate model. The results obtained, especially from 2019 to 2022, will experience fluctuations. In 2019, the company PT. Garuda Tbk is included in the healthy category, in 2020 and 2021 it will be included in the type prone to bankruptcy. In 2022, the company will be better and can enter the healthy group.